Indicators of Subarachnoid Hemorrhage as a Cause of Sudden Cardiac Arrest - Joseph Zachariah; Jessica A. Stanich; Sherri A. Braksick; Eelco FM. Wijdicks; Ronna L. Campbell; Malcolm R. Bell; Roger White (Clinical Practice and Cases in Emergency Medicine, 2017)
Subarachnoid hemorrhage (SAH) may present with cardiac arrest (SAH-CA). We report a case of SAH-CA to assist providers in distinguishing SAH as an etiology of cardiac arrest despite electrocardiogram findings that may be suggestive of a cardiac etiology. SAH-CA is associated with high rates of return of spontaneous circulation, but overall poor outcome. An initially non-shockable cardiac rhythm and the absence of brain stem reflexes are important clues in indentifying SAH-CA.